The decline of judicial deference to medical opinion in medical negligence litigation in Malaysia - Jahn Kassim, Puteri Nemie (World Association of Medical Law, 2008)
The decision of the Federal Court of Malaysia in abandoning the Bolam principle in relation to doctor's duty to disclose risks has clearly marked the decline of judicial deference to medical opinion in medical negligence litigation in Malaysia. It is undeniable that the Bolam principle has acted as a gatekeeper to the number of claims against medical practitioners. This has always been seen as necessary to protect the society from unwanted effects of defensive medicine. However, will these changes contribute significantly to the growth of medical negligence cases in Malaysia? This article will trace the development of the Bolam principle in medical negligence litigation in Malaysia since 1965 and analyse the influence of selected Commonwealth cases on the development. The implications of the Federal Court ruling will also be discussed.